Contributions of source population and incubation temperature to phenotypic variation of hatchling Chinese skinks. Issue 3 (23rd October 2020) - Lu, Hong-Liang; Qu, Yan-Fu; Li, Hong; Ji, Xiang
Abstract: Phenotypic plasticity and local adaptation are viewed as the main factors that result in between-population variation in phenotypic traits, but contributions of these factors to phenotypic variation vary between traits and between species and have only been explored in a few species of reptiles. Here, we incubated eggs of the Chinese skink ( Plestiodon chinensis ) from 7 geographically separated populations in Southeast China at 3 constant temperatures (24, 28, and 32 °C) to evaluate the combined effects of clutch origin, source population, and incubation temperature on hatchling traits. The relative importance of these factors varied between traits. Nearly all examined hatchling traits, including body mass, snout–vent length (SVL), tail length, head size, limb length, tympanum diameter, and locomotor speed, varied among populations and were affected by incubation temperature. Measures for hatchling size (body mass and SVL) varied considerably among clutches. Source population explained much of the variation in hatchling body mass, whereas incubation temperature explained much of the variation in other examined traits. Our results indicate that between-population variation in hatchling traits of P. chinensis likely reflects the difference in natural incubation conditions and genetic divergence.